Ice saturation at the tropopause observed from the ER-2 aircraft - Murphy, D. M.; Kelly, K. K.; Tuck, A. F.; Proffitt, M. H.; Kinne, S. (1990)
Ice saturation at or just above the tropopause was frequently observed during the ER-2 vertical profiles over Stavanger (59 deg N) during the Airborne Arctic Stratospheric Expedition (AASE). On occasion, ice saturation extended as much as 500 m above the tropopause. Saturation was not observed over Punta Arenas (53 deg S) during the Airborne Antarctic Ozone Experiment. Saturation extending just above the tropopause was observed at Moffett Field (38 deg N) in winter but not in summer. The top of a thick cirrus layer at the tropopause will be very strongly cooled, and a thin cloud layer at the tropopause will either be strongly heated or cooled depending on the presence of lower level clouds. Some ER-2 data suggests removal of water and nitrogen species from the tropopause.